2011
DOI: 10.1002/app.34681
|View full text |Cite
|
Sign up to set email alerts
|

Photo‐fabricated unsaturated polyester resin composites reinforced by kenaf fibers, synthesis and characterization

Abstract: New bio-fiber composites (UPRC) cured by ultraviolet radiation were produced using kenaf fiber as reinforcing agent and unsaturated polyester resins as matrix in the presence of styrene and IRGACURE 1800 as photoinitiator. Unsaturated polyester resins based on palm oil were prepared from various ratios of monoglyceride (MG)/maleic anhydride (MA) by the interaction of the corresponding MG monomer, with different equivalents of MA, in the presence of 2-methylimidazole as catalyst. The various characteristics of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…As observed in the DTG profile, UPR/fabric composites have two thermal degradation stages. The first degradation stage belongs to the decomposition of cellulosic fibers, and the second one is attributed to the pyrolysis of unsaturated polymer resin . The T max1 and T max2 represent the temperatures for the weight loss at the first and the second maximum rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As observed in the DTG profile, UPR/fabric composites have two thermal degradation stages. The first degradation stage belongs to the decomposition of cellulosic fibers, and the second one is attributed to the pyrolysis of unsaturated polymer resin . The T max1 and T max2 represent the temperatures for the weight loss at the first and the second maximum rates, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The gel contents of UPRs were tested by Soxhlet extraction to determine the effects of LbL modification on the crosslinking density. 41 The samples were weighed and extracted using toluene as the solvent for 24 h. The gel content was calculated by the formula: gel content% = (W 2 /W 1 ) × 100%; W 1 and W 2 represent the weight of the sample before and after extraction, respectively. From Table 1, it is clearly found that the gel content of UP-3 is lowest.…”
Section: Methodsmentioning
confidence: 99%
“…By the way, this short curing time should also be beneficial to reduce the emission of styrene usually used as reactive diluent and which presents safety issues. However, only few works reported the use of light for such purpose . For example, ultraviolet (UV)‐curing was used to replace the thermally cured resins for repairing damaged reinforced concrete .…”
Section: Introductionmentioning
confidence: 99%
“…However, only few works reported the use of light for such purpose. [1][2][3][4][5][6][7][8][9] For example, ultraviolet (UV)-curing was used to replace the thermally cured resins for repairing damaged reinforced concrete. 3,10,11 The UV-cured fiber-reinforced polymer was also developed for pipes repairing.…”
Section: Introductionmentioning
confidence: 99%
“…15 It is thus a wellmastered technology when it comes to coatings or thin films, but it needs adjustments to be geared to the curing of thick materials. Some academic works successfully describe the manufacturing of glass-fibers reinforced polymers using UV-curing, [16][17][18] but only a few have been interested in the mechanical properties of the obtained materials and even less in a comparison with their thermal equivalents. Among them, Zhang et al 19 showed how to overcome the problem of the limited thickness of photocomposites by applying a stepwise process for the manufacturing glass fiber/acrylate composite using 3 wt % of benzyldimethylketal as photoinitiator.…”
mentioning
confidence: 99%